2016
DOI: 10.4103/1305-7456.175681
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the accuracy of extraoral periapical radiography in root length determination

Abstract: Objective:To determine the accuracy of extra oral periapical radiography in obtaining root length by comparing it with the radiographs obtained from standard intraoral approach and extended distance intraoral approach.Materials and Methods:It was an in vitro, comparative study conducted at the dental clinics of Aga Khan University Hospital. ERC exemption was obtained for this work, ref number 3407Sur-ERC-14. We included premolars and molars of a standard phantom head mounted with metal and radiopaque teeth. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…They found 75% magnification accuracy using EOPA technique, in open-mouth approach with angulations of −25 ± 5° for maxillary and −15 ± 5° for mandibular teeth. Nazeer et al 19 in an in vitro study on mannequin heads found an accuracy of 82.6% using EOPA technique, when the X-ray cone was angled −20 to −30° for maxillary posterior teeth and +20 to +30° for mandibular posterior teeth from the horizontal plane. Zafar and Javed 1 in an in vivo comparative study between IOPA and EOPA techniques with actual WL on premolars found that when the X-ray cone was angled at –35° from horizontal plane and perpendicular to the film on the opposite side of the face, a majority of extraoral radiographs (86%) determined average tooth length accurately with magnification error of less than 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found 75% magnification accuracy using EOPA technique, in open-mouth approach with angulations of −25 ± 5° for maxillary and −15 ± 5° for mandibular teeth. Nazeer et al 19 in an in vitro study on mannequin heads found an accuracy of 82.6% using EOPA technique, when the X-ray cone was angled −20 to −30° for maxillary posterior teeth and +20 to +30° for mandibular posterior teeth from the horizontal plane. Zafar and Javed 1 in an in vivo comparative study between IOPA and EOPA techniques with actual WL on premolars found that when the X-ray cone was angled at –35° from horizontal plane and perpendicular to the film on the opposite side of the face, a majority of extraoral radiographs (86%) determined average tooth length accurately with magnification error of less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the radiographic images did not show any dimensional inaccuracy using EOPAR technique as suggested by some authors. 19 In patients with exaggerated gag reflex, the extraoral technique was found to be a more comfortable imaging procedure. With regard to its diagnostic utility, EOPAR can be used in pediatric patients with noncompliance for placement of sensors, reducing errors while receptor positioning during IOPA procedure and therefore reducing multiple X-ray exposures.…”
Section: Discussionmentioning
confidence: 99%
“…An exaggerated gag reflex is a problem for effective carrying out any dental manipulations: diagnostic, hygienic, therapeutic, and surgical. [ 1 ] The overall prevalence of gagging during dental treatment is up to 8.2%. [ 2 ] Pharmacological sedation is one of the effective ways of prevention of gag reflex development during dental treatment.…”
Section: Introductionmentioning
confidence: 99%